Immunosuppressive Myeloid Cells’ Blockade in the Glioma Microenvironment Enhances the Efficacy of Immune-Stimulatory Gene Therapy - Kamran, Neha (2017)
Survival of glioma (GBM) patients treated with the current standard of care remains dismal. Immunotherapeutic approaches that harness the cytotoxic and memory potential of the host immune system have shown great benefit in other cancers. GBMs have developed multiple strategies, including the accumulation of myeloid-derived suppressor cells (MDSCs) to induce immunosuppression. It is therefore imperative to develop multipronged approaches when aiming to generate a robust anti-tumor immune response. Herein, we tested whether combining MDSC depletion or checkpoint blockade would augment the efficacy of immune-stimulatory herpes simplex type-I thymidine kinase (TK) plus Fms-like tyrosine kinase ligand (Flt3L)-mediated immune stimulatory gene therapy. Our results show that MDSCs constitute >40% of the tumor-infiltrating immune cells. These cells express IL-4Rα, inducible nitric oxide synthase (iNOS), arginase, programmed death ligand 1 (PDL1), and CD80, molecules that are critically involved in antigen-specific T cell suppression. Depletion of MDSCs strongly enhanced the TK/Flt3L gene therapy-induced tumor-specific CD8 T cell response, which lead to increased median survival and percentage of long-term survivors. Also, combining PDL1 or CTLA-4 immune checkpoint blockade greatly improved the efficacy of TK/Flt3L gene therapy. Our results, therefore, indicate that blocking MDSC-mediated immunosuppression holds great promise for increasing the efficacy of gene therapy-mediated immunotherapies for GBM.